The Title ’Gus’ The Title ’Gus’ from the Perspective of X Social Media Users in Indonesia: A Cognitive Linguistics Study and Its Implementation in Critical Literacy Learning - Bagus Triadi, Rai; Hilaliyah, Hilda; Hilaliyah, Widyapuri (IJORER : International Journal of Recent Educational Research, 2025)
His study examines emerging perspectives on the term Gus on social media, particularly on the X platform in Indonesia. Traditionally, Gus carries a positive connotation within Indonesian Islamic culture, symbolizing individuals of moral integrity and religious devotion. However, this perception has shifted following a viral incident involving Gus Miftah, who was accused of insulting a tea seller during a religious event. The controversy sparked public debate and criticism, reshaping how the title is viewed online.Using a qualitative descriptive method, this research collected and analyzed posts containing the keyword Gus to explore how the term’s meaning has evolved. The study is grounded in cognitive linguistics, focusing on imaginative processes such as model manipulation, cognitive planning, image schemas, and semantic interpretation.Findings reveal that Gus is no longer universally regarded as a symbol of piety, but increasingly perceived as a title used for personal or political interests. Public discourse now questions the legitimacy and moral authority of individuals bearing the title, reflecting broader skepticism toward religious figures.The results contribute to the development of teaching materials for Critical Discourse Analysis, helping students identify power dynamics and ideological bias in language. This study highlights how digital platforms shape public perception and demonstrates the role of language, power, and ideology in constructing meaning in online spaces